PREDATION OF THE ORIENTAL NARROW-MOUTHED FROG (Microhyla orientalis Matsui, Hamidy, and Eto, 2013) BY THE FRESHWATER CRAB (Parathelphusa convexa De Man, 1879) IN JAVA, INDONESIA - Rury Eprilurahman; Cahyandra Anggoro; Hastin Asti; Noorman Fauzy; Boggy Sanjaya (BRIN Publishing (Penerbit BRIN), 2025)
We report the first documented observation of predation by the freshwater crab Parathelphusaconvexa on the Oriental narrow-mouthed frog Microhyla orientalis in Indonesia. The event occurred ina rice field in Sleman, Daerah Istimewa Yogyakarta, at night, providing direct evidence that P. convexacan act as an opportunistic predator of small anurans inhabiting agricultural wetlands.